Relation of parental rejection with self-esteem and life satisfaction of young adults (Dhaka University Journal of Biological Sciences, 2014)
The present study was designed to study the relation of parental rejection with self?esteem and life satisfaction. A total of 30 males and 30 females were selected purposively from Dhaka city. Correlation analysis indicated that paternal? and maternal rejection had significant negative correlation with selfesteem and life satisfaction. Adjusted R² of regression analysis indicated that parental rejection was the most important predictor which explained 70.4% of self?esteem and 25.6% variance of life satisfaction. Parental rejection greatly influence in offsprings self?esteem and life satisfaction. Self?esteem is more influenced by parental rejection than life satisfaction. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19828 Dhaka Univ. J. Biol. Sci. 23(1): 69-76, 2014